Inotuzumab ozogamicin in the treatment of relapsed/refractory acute B cell lymphoblastic leukemia - Uy N; Nadeau M; Stahl M; Zeidan AM (Journal of Blood Medicine, 2018)
Natalie Uy, Michelle Nadeau, Maximilian Stahl, Amer M Zeidan Section of Hematology, Department of Internal Medicine, Yale School of Medicine, New Haven, CT, USAAbstract: The improvement in outcomes of adult patients with acute lymphoblastic leukemia (ALL) has been modest, with the exception of Philadelphia chromosome-positive disease, despite advances in supportive care and stem cell transplantation. The recent approvals of novel agents, including the bispecific T-cell engager blinatumomab, the antibody-drug conjugate inotuzumab ozogamicin, and chimeric antigen receptor T-cell products are changing the management of B-ALL, which traditionally relied on chemotherapy-based approaches. Inotuzumab ozogamicin is a humanized CD22 monoclonal antibody linked to the cytotoxic agent calicheamicin. CD22 is expressed on leukemic blasts in >90% of ALL patients, and inotuzumab ozogamicin has shown excellent clinical activity even among heavily pretreated relapsed/refractory (R/R) B-ALL patients and elderly B-ALL patients. Clinical trials have shown superior survival with the drug over chemotherapy-based approaches in the first- or second-line salvage therapy for relapsed B-ALL as monotherapy. Currently, new trials are evaluating inotuzumab ozogamicin in the frontline setting in combination-based approaches. In this review, we summarize the preclinical and clinical data of inotuzumab ozogamicin in R/R B-ALL and foresee the future use of this drug in the clinic.Keywords: inotuzumab ozogamicin, CD22, monoclonal antibodies, acute lymphoblastic leukemia, antibody-drug conjugate